(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the level of acceptance and identify factors associated with the intention and actual use of stainless steel crowns among dental students based on the technology acceptance model. Subject and methods: A cross-sectional descriptive study was conducted among 372 dental students from 10 dental training institutions in Vietnam. A 16-item questionnaire was used to evaluate five constructs: perceived usefulness, perceived ease of use, attitude, behavioral intention, and actual use. Results: Students reported high perceived usefulness of stainless steel crowns (80.2 ± 15.5%) and strong behavioral intention to use them (80.9 ± 14.4%). However, perceived ease of use (54.3 ± 22.0%) and actual clinical use (49.2 ± 22.8%) remained limited. The overall acceptance score was 66.5 ± 12.2%, predominantly at a moderate level. Acceptance levels differed significantly across training institutions (p = 0.046). In regression analysis, behavioral intention showed the strongest association with actual use (β = 0.19; p < 0.001), and the model explained 46% of the variance in actual use. Conclusion: Despite high intention to use stainless steel crowns, actual clinical practice remains limited; therefore, enhanced supervised clinical exposure is warranted to bridge the gap between intention and behavior.